THE ROLE OF FEEDBACK IN THE DESIGN OF A TESTING MODEL FOR SOCIAL JUSTICE (Journal of Contemporary Philology, 2020)
Internationalization of higher education has resulted in an increased establishment of English medium instruction (EMI) courses at non-Anglophone universities. Due to the growing concerns about non-native English speaking lecturers’ ability to teach in English, universities have started implementing policies enforcing assessment of EMI lecturers’ English proficiency. However, research on the effectiveness and the social consequences of these assessments remains limited, especially in terms of the power imbalances such assessments may create at the university workplace. Based on the principle that the oral English proficiency certification should provide benefits for, instead of simple exclusion of, test-takers who have less-advantaged starting position, i.e., lecturers with lower English proficiency (Davies 2010), the article argues that the language assessment models for EMI certification should put emphasis on the formative feedback, and, thereafter, proposes what may be considered relevant and effective feedback content. The discussion in this article is based on the results from a mixed-methods study that examines the utility of the language-related feedback for test-takers, at two non-Anglophone universities, who took a performance-based oral English proficiency test for EMI certification. Three main data collection procedures were undertaken: reports with written feedback and two surveys. Results suggest that the test-takers found the aspects of the feedback that grounded their English language uses in the EMI domain useful and appreciated the opportunity to discuss their challenges and uncertainties during oral feedback session.
Keywords: language tests; EMI; feedback; social justice; EMI certification